The Monument and the Reconstruction of Memory: The Case of Athens, from 19th Century to the Present - Chanratanapreeda, Promchan (Journal of Architectural/Planning Research and Studies (JARS), 2015)
This paper investigates the implication of the monument in architecture and planning concerning its function and potential in modern discourse from the beginning of 19th century. The study focuses on ruins of urban artefacts that become a memorial representation of the past civilisation, more importantly, be beneficial to those associated with the process. To better understanding, since the Acropolis is viewed as a symbol of the classical spirit and civilisation of Western culture with the great architectural aesthetic of Ancient Greek, three Athenian urban projects are taken as a case study, namely, ‘the new Athens’ master plan’ of the 19th century, ‘landscaping around Acropolis’ by Dimitris Pikionis of the 1960s, and the current proposal ‘Rethink Athens’. By collecting and analysing related maps, images and scholarly writings, the paper formulates an argument that traces of Ancient Greek have been evident in the urban development processes of Athens in the modern era. From the construction of national image in the early 19th century, the conservation through aesthetic creativity during the mid-20th century, to the commercialisation of urban space in the present time, the exploration of three projects serves as an explanation of the multiple roles of the monument in different circumstances. This examination reveals that orders and forms of urban fabric are substantially involved political forces, individual attitude, and economic condition. Against the notion of prolonging and representing societal values, the original meaning of the monument is obscured and distorted. In truth, the function of the monument depends on the desires of those associate with an authority or hegemonic power at a certain time. As a consequence, what visitors pursue is the ever-changing meaning of the monument rather than the fixed one.